POTENSI HERITAGE YANG DIMILIKI OLEH DESA WISATA TAMKESI KABUPATEN TIMOR TENGAH UTARA SEBAGAI DAYA TARIK WISATA - Taolin, Arichtia Praevianti; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 4 No 2 (2016): VOL 4, NO 2 (2016): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i02.p16, 2016)
This research analyzed the rural heritage tourism development strategy in Tamkesi, North Cental Timor Regency as a tourism destination. This research uses qualitative approaches. Data collected by observation, in-depth interviews, and literature study. This research used qualitative data analysis. The informant collection techniques used purposive sampling. Tamkesi Traditional Village has tangible heritage and untangibile heritage which can become a tourism main attraction. The results showed that tourism potentials of the village of Tamkesi such as natural tourism resources, accessibility and some tourism facilities and infrastructure are inadequate. Strategies that can assist in developing cultural tourism in rural area heritage in Tamkesi Village are: by knowing the type of cultural amenities in Tamkesi village, that were tangible and intangible heritage facilities. The tourism potentials of the village of Tamkesi among others natural tourism resources, cultural, heritage, accessibility and supporting facilities which have not been packed and managed well, and some tourism facilities and infrastructure are inadequate.
Keywords: Heritage, potential, rural tourism, Tamkesi.